Análisis de ciclo de vida puerta a puerta del proceso de producción de biodiesel a partir de aceite crudo de palma - Benedetti Marquez, Elissa B. (Ingenierias, 2017)
Biodiesel is a completely natural and renewable fuel that can be used in any application where petrodiesel and is manufactured using hundred percent vegetable oil. In this document the life cycle analysis (LCA) applies to a process of producing biodiesel from palm oil, was designed and simulated a continuous process of alkaline transesterification of crude palm oil for biodiesel production using the process simulator Aspen UnisimDesign TecnologyInc R390 was used SIMAPRO 7.1 and Ecoinvent software as a database for life cycle analysis of biodiesel. Evaluation was performed technology and efficiency to establish a (LCA) with the impact categories such as climate change, acidification, eutrophication and non-renewable energy category in this process and thus see their benefits and limitations techniques, also by environmental data obtained we made a comparison between biodiesel from crude palm oil and diesel obtained by refining oil, to assess its contribution to environmental change.